The crack behavior and delamination mechanisms of air plasma sprayed thermal barrier coatings under ultrasonic plasma jet at 1600 °C. Issue 9 (August 2023) - Cai, Huangyue; Shan, Xiao; Lu, Jie; Luo, Lirong; Cai, Zhenwei; Wang, Weize; Zhang, Xiancheng; Zhao, Xiaofeng
Abstract: In this contribution, the performance and delamination mechanisms of air plasma sprayed (APS) yttria stabilized zirconia thermal barrier coatings (YSZ TBCs) under high intensity heat flux at 1600 °C was investigated. The plasma jet was adopted as the heat source with a combination of high temperature and high-speed jet-stream erosion. It was found that the YSZ topcoat would exfoliate when the vertical crack connected to the interior (interfacial/shear) cracks to form a free edge, which turned the mixed-mode buckle delamination into a mode I cracking. The thermo-mechanical analysis indicated that energy release rate associated with the transient cooling was the driving force for the interfacial cracks, while the vertical cracks were developed by the tensile stress during cooldown. The findings obtained in this study implied that the YSZ TBCs can be used for the thermal protection of combustor in ramjet engines.